Evaluating the Kyoto guidelines’ worrisome features and high-risk stigmata to predict high-grade dysplasia and invasive cancer in intraductal papillary mucinous neoplasms - Levine, Jonah M.; Habib, Joseph R.; Rompen, Ingmar F.; Hewitt, D. Brock; Kaplan, Brian; Morgan, Katherine A.; Kluger, Michael D.; Wolfgang, Christopher L.; Javed, Ammar A.; Sacks, Greg D. (Annals of surgical oncology, 2025)
Background: The 2024 Kyoto guidelines for the management of intraductal mucinous neoplasms (IPMNs) build on previous guidelines that consider worrisome features (WF) and high-risk stigmata (HRS) to recommend surveillance or resection. These new guidelines have not yet been validated. Methods: Patients undergoing pancreatectomy for an IPMN at an academic medical center between 2012 and 2023 were included. IPMNs were categorized as low-grade dysplasia (LGD), high-grade dysplasia (HGD), or invasive carcinoma (IC). Preoperative imaging was used to determine HRS and WF in accordance with the 2024 Kyoto guidelines. We compared IPMNs with LGD to those with HGD or IC using univariate analyses and evaluated logistic regression models with c-statistics. Results: Of 211 patients, 84 (40%) had LGD, 49 (23%) had HGD, and 78 (37%) had IC. Among HRS, obstructive jaundice (p = 0.004), pancreatic duct ≥ 10 mm (p < 0.001), and suspicious or positive cytology (p < 0.001) were significantly associated with HGD/IC. An increasing number of HRS were associated with higher rates of HGD/IC. Among WFs, an abrupt change in the caliber of pancreatic duct with distal pancreatic atrophy (p = 0.001) and cystic growth ≥ 2.5 mm/year (p = 0.033) were significantly associated with higher rates of HGD/IC. Increasing numbers of WFs were also associated with higher rates of HGD/IC. The 2024 Kyoto model showed improved discrimination (area under the curve [AUC] = 0.849) compared with the 2017 Fukuoka model (AUC=0.780, p = 0.06). Conclusion: The risk of HGD/IC in IPMNs increased in a stepwise fashion as the number of WFs increased. The 2024 guidelines represent an advancement over the 2017 guidelines, notably with the inclusion of suspicious cytology as an HRS.